2003
DOI: 10.1002/ajmg.a.20506
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutation in the SLC19A2 gene in an African‐American female with thiamine‐responsive megaloblastic anemia syndrome

Abstract: Thiamine-responsive megaloblastic anemia (TRMA) syndrome is an autosomal recessive disorder characterized by diabetes mellitus (DM), progressive sensorineural deafness, and thiamine-responsive anemia. Mutations in the SLC19A2 gene encoding a high-affinity thiamine transporter protein THTR-1 are responsible for the clinical features associated with TRMA syndrome. We report an African-American female with TRMA-syndrome associated with thyroid disease and retinitis pigmentosa caused by a novel mutation in the SLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
44
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 32 publications
(50 reference statements)
5
44
0
Order By: Relevance
“…This mutation has previously been described in three children from two consanguineous families from Pakistan [3].Diabetes mellitus is non-type 1 in nature with onset from infancy to adolescence. Decrease in insulin requirement with institution of high-dose of thiamine has been reported [4]. This was observed in our case also.…”
supporting
confidence: 84%
“…This mutation has previously been described in three children from two consanguineous families from Pakistan [3].Diabetes mellitus is non-type 1 in nature with onset from infancy to adolescence. Decrease in insulin requirement with institution of high-dose of thiamine has been reported [4]. This was observed in our case also.…”
supporting
confidence: 84%
“…In 1978, a second case was reported by Viana & Carvalho (7). Since then, a number of cases have been described (4,(8)(9)(10)(11)(12)(13). It was postulated that this syndrome is related to defects in thiamine metabolism (1,7,14).…”
Section: Discussionmentioning
confidence: 99%
“…4,27,[56][57][58][59] Although mutations in SLC19A2 are one of the causes of PNDM, 1 the clinical diagnosis of SLC19A2 deficiency is rarely made until the presentation of all syndromic symptoms (i.e. diabetes, anemia, and deafness) and is sometimes unrecognized among patients with early onset diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…diabetes, anemia, and deafness) and is sometimes unrecognized among patients with early onset diabetes. 28,56 Because deafness was the earliest symptoms diagnosed in the disease, reflecting the fact that hearing loss is more recognizable than anemia and diabetes, the results of newborn hearing tests could aid in the differential diagnosis of SLC19A2 deficiency among patients with PNDM to permit an earlier diagnosis, proper treatment, and less mortality. 52,60,61 It has been shown that despite thiamine treatment, insulin dependency can relapse after adolescence in some SLC19A2-deficient patients.…”
Section: Discussionmentioning
confidence: 99%